Islamic radicalism and multicultural politics : the British experience - Abbas, Tahir, 1970- (London : Routledge, 2011)
'The manifestation of an Islamic political radicalism in Britain has been one of the most dramatic developments in recent times.'Islamic radicalism and multicultural politics' explores the nature of this phenomenon by analysing the origins of Islam, its historical contact with Western Europe and Britain and the emergence of an Islamic political radicalism in the Muslim world and in diaspora communities in the West. Tahir Abbas draws on historical analysis and contemporary case setudies to explore the post-war immigration and integration of Muslim groups, the complex relations that exist between a secular neo-liberal Britain and a diverse but multifaceted political and cultural Islam, and the extent of social and economic inequalities that affect Muslims as individuals and citizens in local area communities. He shows how violent extremism among British Muslims is in reality influenced by a range of issues, including the processes of globalisation and contemporary politics, media, culture and society. Examining and dissecting the approaches to public policy, Abbas offers suggestions for tackling the major social, cultural, political and economic questions facing British Muslims in the post-7/7 era. An important contribution to the study of religion, race and ethnicity in modern Britain, this accessible work will be of interest to those working in the fields of sociology, ethnic studies, Islamic studies and political science, as well as policy-makers and practitioners'--Publisher's description, p. [4] of cover.
From the historical to the contemporary -- Islamic political radicalism: origins and destinations -- Post-war immigration: ethnicity, identity and spatiality -- The formation of Muslim capital: education, employment and entrepreneurialism -- Neo-orientalism and Islamophobia: the media and print news -- The political philosophy of multiculturalism and the'modern Muslim' -- Islamist identity politics in the context of globalisation -- Muslims, crime, terror and the law -- British Islam tomorrow and the battle ahead.
Keywords: Muslims -- United Kingdom -- Politics and government; Muslims -- United Kingdom -- Ethnic identity; Muslims -- United Kingdom -- Social conditions; Islamic renewal -- United Kingdom; Islamic fundamentalism -- United Kingdom; Radicalism -- United Kingdom; Islam -- United Kingdom -- Public opinion; Public opinion -- United Kingdom; Great Britain -- Politics and government -- 2007-